313 Modulation of Ca125 expression by htert in ovarian cancer: possible implication of PI3K/Akt/mTOR signaling pathway. (18th September 2019) - Atallah, D; Antoun, S; Moubarak, M; El Kassis, N; Chahine Chahine, G; Hilal, G
Abstract : Objectives: To investigate the possible inter-relationship between Ca125 secretion and telomerase activity, and the possible implication of the PI3K/Akt/mTOR pathway in this modulation. Methods: Ovarian cancer cell lines OVCAR-3, SK-OV-3 and IGROV-1 were treated with three different telomerase inhibitors, BIBR-1532, Costunolide and MST-312, one activator, LPS, and various inhibitors of the PI3K/Akt/mTOR pathway, PI828, wortmanin, GSK692690 and rapamycin. Ca125 expression was quantified by Q-PCR and its secretion by ELISA. Results: The three telomerase inhibitors decreased the Ca125 mRNA expression and protein secretion by the three cell lines. The same pattern was obtained when cells were treated with hTERT siRNA. The activation of hTERT lead to an increase in Ca125 expression and secretion, and to an increase in cell migration and motility. Interestingly, inhibition of PI3K/Akt/mTOR signaling pathway by PI828, wortmanin, GSK692690 and rapamycin lead to a decrease in Ca125 concentration suggesting the involvement of this pathway in Ca125 regulation. Moreover, an additive effect was shown when costunolide and BIBR 1532 were combined with the previous inhibitors. A decrease in telomerase expression and activity was obtained after gene silencing of Ca125 by the three cell lines, along with a decrease in PI3k, Akt and mTOR gene expression, which may explain the possible implication of this signaling pathway in the modulation of hTERT by Ca125. Conclusions: Both inhibition of telomerase and PI3K/Akt/mTOR signaling pathway decreased the Ca125 secretion, while inhibition of Ca125 decreased hTERT expression and activity suggesting a mutual modulation and a substantial role of Ca125 in cancer initiation and progression.